Identity Development & Belief Change: Experiences of Beginning Urban Teachers - Kate Rollert French (Arizona State University, 2020)
Drawing on literature around the first-year experiences of new teachers working in urban schools-including their unique vulnerability for emotional turbulence as they undergo the Moir (1990) First Year Phases of Teaching model-this article examines the changing beliefs of brand new urban educators as they progress throughout their first year as teacher of record. Using the Moje and Luke (2009) theoretical framework for identity formation and development, this study examines how teachers' beliefs and dispositions develop in tandem with a new identity through various social interactions and scenarios.  Findings suggest that new teachers are more likely to change their beliefs when they undergo various stages of emotional conflict and will turn to more experienced colleagues at their new school for advice and insight. This can contribute to belief change and affect classroom practice. Teachers were more likely to change their beliefs during the middle of the school year-specifically during the survival and disillusionment phases of the Moir (1990) model. Implications for teacher induction and development are discussed.